Cardiovascular and metabolic effects of hyperbilirubinemia in a cohort of Italian Olympic athletes - Di Gioia, G.; Crispino, S. P.; Monosilio, S.; Maestrini, V.; Nenna, A.; Segreti, A.; Squeo, M. R.; Lemme, E.; Ussia, G. P.; Grigioni, F.; Pelliccia, A. (Scandinavian Journal of Medicine & Science in Sports, 2023)
Introduction Bilirubin was supposed to have cardio-metabolic protective role by signaling functions. Indeed, mild hyperbilirubinemia has immunosuppressive and endocrine activities and may offer protection against oxidative stress-mediated diseases. Gilbert syndrome (GS) has been hypothesized to provide cardio-metabolic benefits.